The Effect of Wood on Japanese Architecture: The Sample of The Horyu-Ji Temple - Tuğçe Şirikçi (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Traditional Japanese architecture consists of natural wood, hay, earthenware, and similar types of materials. Japanese architecture has a linear structure. The main purpose of Japanese architecture is to be unified. Many of the materials used here have a higher moisture protection function than those made of plywood or spinning. The structure has a breathing mechanism that naturally preserves good air and moisture. The fact that Japan is rich in vegetation has a great effect on the formation of natural materials. There is a bond in Japanese architecture that respects the harmony between human and nature. Human beings are a part of nature. This article refers to the oldest wooden building in the world. The first world cultural heritage in Japanese architecture, and the temple of Horyu-ji, which has been standing for over 1300 years. The aim is to investigate the aesthetic, ethical awareness and ethnology of traditional wood used on Japanese architecture. While the structure and varieties of wood refer to the findings on the buildings, it is an attempt to approach the "lifestyle and values" of the wood form and structure.